PENGARUH GOOD CORPORATE GOVERNANCE, UKURAN PERUSAHAAN, DAN LEVERAGE TERHADAP INTEGRITAS LAPORAN KEUANGAN - Rimi Gusliana Mais; Fadlan Nuari (Universitas Muhammadiyah Malang, 2017)
The purpose of this study is to examine the effect of good corporate governance being inspected toindependent commissioners and institutional ownership, firm size and influence on the integrity of financial statements. The population of this study is a mining company listed on theIndonesia Stock Exchange (BEI) in 2012-2015. The sample is determined by purposive samplingmethod, with total samples of 11 mining companies for total observation in this research are 44observations. The results of this study prove that independent commissioners have a positiveimpact on the integrity of financial statements. As for institutional ownership and leverage havea negative impact on the integrity of financial statements. And firm size proved not to affect theintegrity of financial statements.Ke y wo rds: Company Size, Good Corporate Governance, Integrity of Financial Statement,Leverage